Sistem Informasi Kepegawaian dan Penggajian Karyawan berbasis Web dengan Fitur Selfie dan Pemantauan Lokasi - Kirana, Dinar Mersasi; Riyadi, Aditya Akbar; Susanto, Arief (Jurnal Pendidikan Informatika (EDUMATIC), 2025)
Manual management of personnel and payroll data at Anna Bakery Pati faces obstacles in attendance accuracy, data processing efficiency, and transparency in payroll. This study aims to develop a web-based personnel and payroll information system with the main features of attendance validation using selfie photos and GPS, as well as automatic integration between attendance recording and salary calculation. The development method used is waterfall, which includes the stages of analysis, design, implementation, testing, and maintenance. Data were collected through observation, interviews with company owners, and user surveys using questionnaires. System testing uses the black box method to ensure system functionality and data analysis is carried out based on the results of user surveys. The results of our findings are a web-based personnel and payroll information system equipped with attendance validation features using GPS and selfies, automatic salary calculations, and integrated employee permit and leave management. In addition, the system provides a reporting feature to facilitate access to attendance and salary data. The test results show that the system can function well according to needs and is well received by the owner and employees of Anna Bakery. This system increases transparency in attendance recording, reduces the risk of fraud in attendance, and speeds up the payroll administration process.  With this system, companies can optimize HR management more effectively.